Correlation of Self-Assessment with Attendance in an Evidence-Based Medicine Course - Ramirez-Unwin, M (American Physiological Society, 2015)
In previous studies, correlations between attendance and grades in lectures have given variable results and, when statistically significant, the correlation has been weak. In some studies, a sex effect has been reported. Lectures are a teacher-centered learning activity. Therefore, it appeared interesting to evaluate if a stronger correlation between attendance and grades would occur in a face-to-face "evidence-based medicine" course with few lectures and more time dedicated to active learning methods. Small-group work and peer learning were used to foster deep learning and to engage students in their own learning process. Most of the time, students worked in small groups solving contextualized problems and critically analyzing the quality of published medical literature. Peer learning was also developed in collaborative evaluations, and constant feedback was provided. Therefore, it was hypothesized that high attenders would develop a higher self-perception of learning and obtain higher marks than low attenders. Student self-perceptions of their capacity to apply evidence-based medicine were measured by the application of an online self-assessment survey, and objective learning was measured as the grades obtained in a final accumulative individual test. It was found that male students obtained higher grades and were more confident in their achievements than their female peers, despite male and female student attendance being similar. In addition, attendance was correlated with the perceived capacity to apply evidence-based medicine only in male students and was not correlated with academic outcome.